KONTRIBUSI POWER OTOT TUNGKAI DAN EKSTENSI TUNGKAI TERHADAP HASIL SERVICE ATAS PADA TIM SEPAKTAKRAW PSTI CLUB GESIMA DI KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Jodi Evindra; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is when the service is not optimal, uses strength, does not have good flexibility, the ball is often involved in the net, the ball in service is not properly aimed, the ball is out of service field line, the ball is service is easy to accept for opponents and when doing service, the body or body of the teck often does not follow the direction of the foot falling after doing the service. the aim of this research was to determine the contribution of leg muscle strength and limb extension to the results of top service from the PSTI Desima club team in Kelayang Sub-District Indragiri Hulu, representing 6 samples using puposive sampling techniques. The tools in this study were Standing Broard Jump, front split and top service tests. The data obtained was analyzed when the product correlation was present. Based on the analysis of normality test data, X1 produces LoMax of 0.184 and Ltable of 0.319 and X2 produces LoMax of 0.149 and Ltable of 0.319. while the variable Y yields a LoMax of 0.173 and an Ltable of 0.319, this means LoMax <L table. Based on statistical data analysis, the data is normally distributed. Based on the test requirements of the above analysis, the hypothesis test on the variables X1 and X2 against the Y variable data is 0.961 > 0.878 Rcount> Rtabel data. Thus, there is a contribution of leg muscle strength and limb extension to upper service results in PSTI Decima club sepaktakraw team in Kelayang district. Indragiri Hulu Regency is 92.35%.Key Words: Leg Muscle Strength, Limb Extension, Top Service Results